The Impact Factors of Peripheral Diabetic Neuropathy Which is Along with Hyperglycemia, Hypercholesterolemia, and Hyperaggregation - Citra Amaniah Anhar; Yetti Hernaningsih; Puspa Wardhani, Soebagijo Adi; Mohammad Saiful Ardhi (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objective: The prevalence of T2DM case in 2018 has increased by 10.9%. The majority of T2DMpatients often ignore some of the most important conditions to experience complications, which iscomplications of PDN. This study aims to analyze the dominant factors in PDF patients with hyperglycemia,hypercholesterolemia, and hyperaggregation. Material and methods: This research is a case control studyconducted from April to October 2020. The sample is 85 patients who have been confirmed to have PDNby neurologists aged 40 - 65. Sampling was conducted at several hospitals in Surabaya with a purposivesampling method. Data analysis was conducted in three stages, namely univariate analysis, bivariateanalysis and multivariate analysis. Results: 85 PDN patients who experienced hyperglycemia amountedto 81%, hypercholesterolemia 81%, and hyperaggregation 67%. The dominant factor affecting the threeconditions (hyperglycemia, hypercholeterol, and hyperagregation) in this PDN patient was a history ofhypertension with a value of p = {(0.012); (0.007); (0.001)} and also a long period of suffering from T2DMwith p value = {(0.019); (0.025); (0.041)). Meanwhile, age, gender and regularity for treatment control werenot the dominant influencing factors. Conclusion: Suffered for a long time from T2DM and a history ofhypertension are the main determinants of peripheral diabetic neuropathy which is along by hyperglycemia,hypercholesterolemia, and hyperaggregation.